Interferențe ale esteticii și spiritualității zen în viziunea artistică a lui Andrei Șerban - Giurescu, Victor (Theatrical Research, 2025)
Interferences of Zen Aesthetics and Spirituality in Andrei Șerban’s Artistic Vision In a world marked by an inversion of traditional value systems and an increasingly accentuated cultural plurality (not necessarily axiologically grouped), actors and directors seek to reconfigure the relationship between corporality, intellect, emotion and spirit. This search can be seen as a response to the deep need for meaning, for authenticity, for completing the inner space meant for religiosity. The director Andrei Șerban recalls in his autobiographical work the first meeting with the meditative exercises and awareness related to Zen, teachings that he intuitively experienced since his youth. Later, years later, in a monastery in Japan, the director would find that those felt energies were conceptualized within Zen Buddhism. This sensory experience, symbolized by the ʻwiresʼ that support the being from the bottom up and from the top down, reflects the transition from materiality to spirituality and vice versa, the necessity of the coexistence of the dimensions of materiality and spirituality evoking the ephemerality of the physical body and emphasizing the need for an omnipresent verticality. This verticality will become an essential feature of Andrei Şerban’s entire directorial creation.